2019
DOI: 10.1080/13811118.2018.1472691
|View full text |Cite
|
Sign up to set email alerts
|

Which Chart Elements Accurately Identify Emergency Department Visits for Suicidal Ideation or Behavior?

Abstract: These findings highlight the use of key discrete fields in the medical record that can be extracted to facilitate identification of whether an ED visit was suicide-related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…Inconsistencies in findings may also be attributable to the lack of an internationally accepted protocol for recording data on suicide attempts. In fact, only limited data are available on attempts, based on self-reports in wider community surveys and on descriptions of self-inflicted lesions in the records of hospital emergency departments and other health centers [2,27]. However, it seems that the majority of people who die by suicide or attempt suicide have no previous contact with a mental health center or hospital [7,18], which was observed in only one-third of suicide victims in one study [28].…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistencies in findings may also be attributable to the lack of an internationally accepted protocol for recording data on suicide attempts. In fact, only limited data are available on attempts, based on self-reports in wider community surveys and on descriptions of self-inflicted lesions in the records of hospital emergency departments and other health centers [2,27]. However, it seems that the majority of people who die by suicide or attempt suicide have no previous contact with a mental health center or hospital [7,18], which was observed in only one-third of suicide victims in one study [28].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of service utilization patterns would be affected if patients interacted with institutions outside the scope of Rhode Island's HIE. Future studies would benefit from access to clinical notes given that Arias et al (2019) have shown that ICD codes are a poor indicator of suicide‐related ED visits. Of note, this was a descriptive study that did not directly compare the rates of SI/SB in the unhoused population versus the general population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, analysis of public health trends in child mental health using EHRs often relies on data stored in structured fields, most commonly, International Classification of Disease codes. However, structured data alone is often inaccurate in the discovery of mental health and suicide-related visits [28,29]. There has also been scarce adaptation of natural language processing and other text processing methods to detect child mental health conditions from large-scale EHRs [30].…”
Section: Cohort Discovery Recognizes Patients With Similar Attributesmentioning
confidence: 99%